Estudo da viabilidade econômica para a utilização da semente da euterpe oleracea mart. (açaí) como recurso energético - LUCZYNSKI, Miroslawa (Universidade Federal do Pará, 2011)
This work had as objective the study of the economic viability for the Euterpe oleraceas Mart. (açaí) seed use as energy resource in the city of Belém-PA. Initially, it was realized a field survey of the sail points and quarters of biggest production of açaí, carrying through after that the assays of the termogravimetric properties of the seeds that are: Humidity text, volatile text, cinzas text, fixed carbon text and superior calorific power. The survey points made possible the creation of a data base, using the Microsoft Software Access, which supplies reports with the identification of the proprietors name, as well as the number of bags that is it processes per day, weight of bag and its energy potential. It was used still the Microsoft ARC VIEW, of easy interaction with Access that made possible the creation of an up to date map of the points for the city of Belém-PA. With those data a study of the transport routes was made in the Geographic Information System (GIS) GOOGLE EARTH. There were determined routes, through the Centroid method, which is the point of highest concentration of the variable of study, in this case, the açaís seed, for the transport of biomass to its final destination that is the UFPA, where if it finds the plant that uses the biomass as combustible to generate energy. When calculating the economic viability there were used the plant of Energy and Biomass of the Group of Energy, Biomass and Environment (EBMAs) together with the data of the consumption of electric energy of the UFPA in the period from 06/2006 to 06/2007, finally it was realized a comparison between the values gotten in the two done surveys and the confirmation of how much the UFPA would save in financial and energy terms with the biomass energy use. In conclusion the açaís seed is economically viable as energy resource for energy supply in UFPA, since the cost of supplied electric energy the concessionaire services the CELPA must exceed the cost of the renewable generation system, thus causing an economy in the final value, of the consumption of electric energy.